Assessment of newly introduced foundation course for medical undergraduates: students' vs faculty's perspective - Shalini Sobti; Meeta Gupta; Vanita Gupta; Aditya Gupta; Satish Parihar; Vikrant Singh (Journal of Family Medicine and Primary Care, 2020)
Background and Objectives: In compliance with MCI's recommendation, a month-long Foundation Course was conducted in our institution in Aug'19. The present study was conducted to seek the opinion of the students and faculty regarding relevance of the topics included in the course to enable revisions to be made in designing the course for the subsequent sessions, to make it more effective and student-oriented. Methods: A questionnaire-based cross-sectional study was conducted to seek the opinion of 100 students who underwent the Foundation Course and 35 faculty members who were involved in teaching the topics allotted. Results: Positive feedback was recorded from63% of the students and 69% of the faculty regarding the overall experience of the course. Among the different modules, Skills module was voted as relevant by majority (73%) of students, whereas a module on Enhancement of Language and Computer Skills was found relevant to the course by a mere 52% students. In contrast, module on Sports and Extracurricular activities was adjudged as most relevant while as module on Enhancement of Language and Computer Skills got the least positive feedback (81.43% vs. 60.36%, respectively) from the faculty. Interpretation and Conclusions: Foundation Course recommended by MCI for MBBS students at the entry level is a welcome step. This can further be made more beneficial by making necessary modifications in the planning of the course in light of suggestions received from the participants.